2021
DOI: 10.1111/os.13110
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Internal Fixation Failure of Femoral Peritrochanteric Fracture

Abstract: Objective To investigate the factors, surgical treatment methods and clinical effect of internal fixation failure of intertrochanteric and subtrochanteric fractures. Methods From June 2015 to May 2019, arthroplasty and internal fixation revision were used to treat 18 cases of internal fixation failure of intertrochanteric and subtrochanteric fractures. There were 10 males and eight females, with an average age of 67.3 years (38–92 years). The 16 cases of initial intertrochanteric fractures were classified acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…On reviewing the literature, we found various reasons for failed IT fracture fixation, like implant loosening, screw cut-off, screw penetration into the joint, varus reduction, and unstable fracture pattern. Zhong et al, 18 in their study, concluded that failure of IT fracture fixation following intramedullary nailing was due to unstable fracture pattern, unsatisfied reduction, improper implant position, poor quality of bone, and inappropriate choice of implant.…”
Section: Resultsmentioning
confidence: 99%
“…On reviewing the literature, we found various reasons for failed IT fracture fixation, like implant loosening, screw cut-off, screw penetration into the joint, varus reduction, and unstable fracture pattern. Zhong et al, 18 in their study, concluded that failure of IT fracture fixation following intramedullary nailing was due to unstable fracture pattern, unsatisfied reduction, improper implant position, poor quality of bone, and inappropriate choice of implant.…”
Section: Resultsmentioning
confidence: 99%
“…Fracture reduction can be completed under direct vision, thereby ensuring the effects of reduction and fixation, and creating favorable conditions for early postoperative rehabilitation training. At the same time, the DAA to the hip joint is relatively safe without damaging the blood vessels and nerve tissue in the area surrounding the fracture, which can significantly reduce the incidence of postoperative complications [11] .…”
Section: Discussionmentioning
confidence: 99%
“…They treated 8 of them with revision internal fixation, 4 of them with partial arthroplasty and 6 of them with total arthroplasty. According to their results, they recommend revision of the internal fixation for youngers and arthroplasty surgery for elderly patients to treat a failed internal fixation treatment 25 . D'Arrigo et al treated 21 patients (mean age: 75.8) with failure of trochanteric fracture fixation with partial (n:2) or total hip arthroplasty (n:19).…”
Section: Discussionmentioning
confidence: 99%